The Effect Of Plyometric Push-Up Training On Arm Power Improvement In Male Volleyball Extracurricular Athletes - Albertus Oktaviabo Hendiramadhanny; Agung Wahyudi (Universitas Negeri Semarang, 2026)
This study aimed to determine the effect of plyometric push-up training on arm power improvement in male volleyball extracurricular athletes at SMA PL Don Bosco Semarang. A pre-experimental design with a one-group pretest–posttest approach was employed. Ten male students were recruited through total sampling based on the following inclusion criteria: actively participating in volleyball extracurricular activities for a minimum of three months, physically healthy, and free from musculoskeletal injury. Arm power was assessed using the Medicine Ball Chest Pass Test (MBCPT) with a 2–3 kg medicine ball; the best distance from three valid trials was recorded as the subject's score. The plyometric push-up training programme was conducted over six weeks at a frequency of three sessions per week (Monday, Wednesday, and Friday), progressing from basic plyometric push-ups through clap push-ups, medicine ball push-ups, and explosive push-ups. Descriptive and inferential statistics were applied. Data normality was verified using the Shapiro–Wilk test (p > 0.05). The paired-samples t-test revealed a pre-test mean of 4.305 m (SD = 0.756) and a post-test mean of 5.632 m (SD = 0.944), yielding a mean improvement of 1.327 m (30.82%). The t-statistic was 6.134 (df = 9, p = 0.000), exceeding the critical value of t(0.05, 9) = 2.262. Accordingly, the null hypothesis was rejected. These findings confirm that a six-week plyometric push-up programme produces a statistically significant and practically meaningful increase in arm power in adolescent male volleyball athletes.